PENERAPAN MEDIA PEMBELAJARAN BERBASIS KAHOOT! UNTUK MENINGKATKAN MINAT DAN KEAKTIFAN BELAJAR SISWA KELAS X DI SMA NEGERI 1 SAMATURU - Qalbi, Nur; Ainun Mardatilla; Ribbi Il Fitri; Fitrya L. Fadly; Ivank Permana; Muh. Fachrul; Muh. Alwi Suhajardita; Marniati; Slamet Hariyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the application of Kahoot!-based learning media to increase students' learning interest and activeness in the learning process in class X of SMA Negeri 1 Samaturu. This research used a quantitative approach. The research subjects were students of class X at SMA Negeri 1 Samaturu. Data were collected using a questionnaire distributed to students after the implementation of learning using Kahoot! media. The questionnaire used a Likert scale consisting of several response options. The data obtained were analyzed using descriptive percentage analysis to determine students’ responses to the use of Kahoot! in learning activities. The results showed that the average percentage of student responses to the use of Kahoot! learning media was 85% with a very good category. The results also indicated that the aspects of students’ learning interest obtained a percentage of 85%, student activeness in learning 83%, students’ interest in Kahoot! media 87%, and ease of understanding the material 84%. These results indicate that the use of Kahoot! as a learning media can increase students’ learning interest, activeness, and understanding of the material. Therefore, Kahoot! can be used as an innovative and interactive learning media to support a more effective and engaging learning process.